CASE REPORT: AORTIC PSEUDOANEURYSM POST AORTIC VALVE REPLACEMENT (Vietnam Journal of Community Medicine, 2026)
Aortic pseudoaneurysm formation post aortic valve replacement is one of the rare and devastating complications post valve replacement. Aortic pseudoaneurysm can occur few weeks or month after surgery. The spectrum of symptoms varies from dyspnea, chest pain, and fever. However, in rare cases, aortic root aortic pseudoaneurysm could be asymptomatic. Aortic pseudoaneurysm mortality could be very high if left untreated. We report 2 cases of patients admitted with hemoptysis, chest pain, and low-grade fever after aortic valve replacement surgery and were diagnosed by CT and successfully managed with resection of pseudoaneurysm and ascending aorta replacement.
Keywords: Aortic pseudoaneurysm, aortic valve replacement.